Ultrasonic echo reinforcement for the blind - Orlowski, Rafal John (1976)
The ability that many blind people develop of detecting near objects by means of echo-location is well known. This investigation is concerned with the development of an aid that will enhance this ability by transmitting ultrasonic pulses into the environment and receiving the echoes returning from surrounding objects. The echoes are detected and heard as clicks by the user, who is able to determine the direction from which the sound is coming by using his natural localisation ability. Further, the clicks are "coded" by switching the receivers on and off, so that the rate of clicking indicates the distance of an object.